2020
DOI: 10.18203/2320-1770.ijrcog20203866
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of menopausal symptoms and its association with various factors among women in post menopausal age group: a cross-sectional study

Abstract: Background: Menopause is an important time in women's life and it is a natural event in the process of aging. The onset of menopause heralds a time of diminished estrogen exposure, which may have both acute and chronic effect on health and quality of life.Methods: It was a cross sectional study, conducted for a period of 3months i.e. June to August 2018 among post menopausal women in 8 selected villages with a sample size of 247.Results: The common post- menopausal symptoms were joint and muscular discomfort, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…A study in Shiraz, Iran, showed that a good improvement in quality of life is caused by educational intervention because education could decrease the problems or symptoms of the menopause stage and lower their intensity (27). A high risk factor for vasomotor symptoms was considered to be low educational status (28). Economic status also plays a role in the onset of menopause, which will undoubtedly affect their quality of life.…”
Section: Sociodemography Factorsmentioning
confidence: 99%
“…A study in Shiraz, Iran, showed that a good improvement in quality of life is caused by educational intervention because education could decrease the problems or symptoms of the menopause stage and lower their intensity (27). A high risk factor for vasomotor symptoms was considered to be low educational status (28). Economic status also plays a role in the onset of menopause, which will undoubtedly affect their quality of life.…”
Section: Sociodemography Factorsmentioning
confidence: 99%
“…Menopause is the term stated about the phase in which a woman experiences a lot of changes in the body prior to or after the cessation, i.e., cessation of a period of reproduction. It is the term where periods stop for a year and ovarian function also stops which results in permanent amenorrhoea 1 . Menopause is the aging stage and it also progresses the process of non -non-communicable conditions.…”
Section: Introductionmentioning
confidence: 99%